Conservation and global distribution of non-canonical antigens in Enterotoxigenic Escherichia coli. - F Matthew Kuhlmann; John Martin; Tracy H Hazen; Tim J Vickers; Madeline Pashos; Pablo C Okhuysen; Oscar G Gómez-Duarte; Elizabeth Cebelinski; Dave Boxrud; Felipe Del Canto; Roberto Vidal; Firdausi Qadri; et al. (Public Library of Science (PLoS), 2019)
Background Enterotoxigenic Escherichia coli (ETEC) cause significant diarrheal morbidity and mortality in children of resource-limited regions, warranting development of effective vaccine strategies. Genetic diversity of the ETEC pathovar has impeded development of broadly protective vaccines centered on the classical canonical antigens, the colonization factors and heat-labile toxin. Two non-canonical ETEC antigens, the EtpA adhesin, and the EatA mucinase are immunogenic in humans and protective in animal models. To foster rational vaccine design that complements existing strategies, we examined the distribution and molecular conservation of these antigens in a diverse population of ETEC isolates. Methods Geographically diverse ETEC isolates (n = 1159) were interrogated by PCR, immunoblotting, and/or whole genome sequencing (n = 46) to examine antigen conservation. The most divergent proteins were purified and their core functions assessed in vitro. Results EatA and EtpA or their coding sequences were present in 57.0% and 51.5% of the ETEC isolates overall, respectively; and were globally dispersed without significant regional differences in antigen distribution. These antigens also exhibited >93% amino acid sequence identity with even the most divergent proteins retaining the core adhesin and mucinase activity assigned to the prototype molecules. Conclusions EtpA and EatA are well-conserved molecules in the ETEC pathovar, suggesting that they serve important roles in virulence and that they could be exploited for rational vaccine design.